Barkas effect in stopping of fast diclusters in solids. Issue 1 (1st February 2016) - Wilson, Tyler; Mišković, Z.L.
Abstract : We study the stopping of a fast proton dicluster moving through a metal target with an electron gas described by a hydrodynamic model. Both the first-order and the second-order expressions are derived and computed for the total stopping force on the cluster, giving a nonlinear correction of the Barkas type. Results are shown as functions of the cluster speed and the interproton distance in the cases of a randomly oriented dicluster and a colinear dicluster consisting of two protons aligned in the direction of motion. We find that the Barkas correction increases the overall stopping force, especially at lower speeds and shorter interproton distances. While the Barkas correction is found to accentuate interferences in the vicinity effect for colinear diclusters, it presents an insignificant contribution to the vicinity effect for randomly oriented diclusters.